THE EFFECT OF TWO SCIENCE PROGRAMS (ESS AND LAIDLAW) ON STUDENT CLASSIFICATION SKILLS, SCIENCE ACHIEVEMENT, AND ATTITUDES. - Vanek, Eugenia Poporad; Montean, John J. (Journal of Research in Science Teaching, 1977)
The article compares the effect of an activity-based curriculum, the Elementary Science Study (ESS) and a textbook approach, the Laidlaw Science Series, on the classification skills, science achievement and scientific attitudes of students. It indicates that the teaching method or materials failed to make a difference in the classification ability, science achievement or attitude of the students. However, the results of the study has an important implication for teaching. The assumptions that ESS differs from the textbook classroom are not confirmed.